Bridging Evolutionary Biology and Developmental Psychology: Toward An Enduring Theoretical Infrastructure. Issue 6 (16th January 2018) - Frankenhuis, Willem E.; Tiokhin, Leonid
Abstract : Bjorklund synthesizes promising research directions in developmental psychology using an evolutionary framework. In general terms, we agree with Bjorklund: Evolutionary theory has the potential to serve as a metatheory for developmental psychology. However, as currently used in psychology, evolutionary theory is far from reaching this potential. In evolutionary biology, formal mathematical models are the norm. In developmental psychology, verbal models are the norm. In order to reach its potential, evolutionary developmental psychology needs to embrace formal modeling.